Pengaruh Variabel Keuangan dan Non Keuangan terhadap Underpricing pada Perusahaan yang Melakukan Initial Public Offering (IPO) di Bursa Efek Indonesia - Rianty N, Martha; Riana, Dwi (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
Underpricing is a phenomenon in initial public offering that often occurs in the capital market and has been proven by research in many countries. This study aims to analyze financial and non-financial factors that effect underpricing. This research is done in Indonesia stock exchange specifically on those companies that are going on initial public offering in 2010-2015. Underpricing is measured using intial abnormal return which is the dependent variable of this study. Meanwhile the independent variables are financial leverage (financial variable), auditor reputation, underwriter reputation, (non-financial variables). 114 companies are selected as the sample through purposive sampling method. Logistic regression model is used to test the relationship between the variables. The results show that the reputation of underwriter and auditor are significant and positive in affecting the underpricing. Meanwhile, financial leverage are found to be insignificant in affecting the underpricing.